2018
DOI: 10.2197/ipsjjip.26.396
|View full text |Cite
|
Sign up to set email alerts
|

Access Control Mechanism to Mitigate Cordova Plugin Attacks in Hybrid Applications

Abstract: Hybrid application frameworks such as Cordova are more and more popular to create platform-independent applications (apps) because they provide special APIs to access device resources in a platform-agonistic way. By using these APIs, hybrid apps can access device resources through JavaScript. In this paper, we present a novel apprepackaging attack that repackages hybrid apps with malicious code; this code can exploit Cordova's plugin interface to steal and tamper with device resources. We address this attack a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…App-repackage attack Kudo et al [9] have presented a novel app-repackaging attack that repackages Cordova apps with malicious code and have proposed a novel runtime access control mechanism that restricts access based on the mobile user's judgment, to present a novel app-repackaging attack that repackages hybrid apps with malicious code.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…App-repackage attack Kudo et al [9] have presented a novel app-repackaging attack that repackages Cordova apps with malicious code and have proposed a novel runtime access control mechanism that restricts access based on the mobile user's judgment, to present a novel app-repackaging attack that repackages hybrid apps with malicious code.…”
Section: Related Workmentioning
confidence: 99%
“…Although WebView can use only Google Safe Browsing, this measure alone is not enough to protect web access via WebView, especially from fake virus alerts, which use malvertising to redirect the users to web pages and scam the users into installing the suspicious Android app. Moreover, previous studies have reported attacks exploiting WebView and presented countermeasures against these attacks [4][5][6][7][8][9][10][11][12][13][14][15][16]. Some studies have presented access control methods to prevent malicious JavaScript codes from exploiting the vulnerabilities of WebView [6][7][8] and to prevent app-repackage attacks in Cordova-based hybrid applications [9].…”
Section: Introductionmentioning
confidence: 99%